The recovery of freedom - Ahmad, Borhanuddin (Dhaka : Hakkani Publishers, 2001)
Autobiography of a bureaucrat from Bangladesh.
Newaz
Keywords: Statesmen -- Bangladesh -- Biography; Bangladesh -- politics and government